Study of Termites’ Life - Oryakhail, Qudratullah (Journal of Natural Sciences – Kabul University, 2021)
Termites are social insects with colonies comprising six castes: winged adults, queen, king, complementary castes, workers, and soldiers. The primary diet of termites includes cellulose-rich materials such as wood, mango, sugarcane, and potato. They commonly live underground, though their earthen mounds are visible above the surface. The termite colony functions efficiently through a division of labor between reproductive and sterile castes. Termites cause extensive damage to wood structures, furniture, wooden poles, and various household items. They also harm crops such as mango, apple, coconut, sugarcane, cotton, potato, wheat, tea, and coffee. In some cases, termites compromise the structural integrity of buildings and railway yards by tunneling beneath them. Subterranean termites also play an ecological role by aerating soil and adding nutrients.